EKSPLORASI KONSEP GEOMETRI JENJANG SMP PADA MOTIF SARUNG SAMARINDA - Nur Fathaillah Pajrin; Haeruddin Haerudin; Sugeng Sugeng (Universitas Muhammadiyah Semarang, 2022)
Samarinda sarong is a masterpiece or specal craft that lived in Samarinda city and one of the most icon from this city. This culture should be able to give attention to the people of Samarinda, because through education based on local wisdom it is able to grow the love of students to preserve the culture in which they live. This research purposed to find out junior high school geometry concept that found from activitiy crafter Samarinda sarong. The method that used in this research is qualitative research method with an ethnographic approach. Research data were collected using documentation techniques in one of the most procduction Cahaya Samarinda in RT.07 Tenun Village with research subject is Samarinda sarong and research object is geometry concept form junior high school. Data analysis was carried out by data collection, data reducting, presenting data after have reducted, making conclusions, and then presented in detail by linking supporting theories. Form explore result have found geometry concepts junior high school as lines, geometry shapes, symmetry, congruence, and similarity.